Transparent Memory Tests Based on the Double Address Sequences - Ireneusz Mrozek; Vyacheslav N. Yarmolik (Entropy, 2021)
An important achievement in the functional diagnostics of memory devices is the development and application of so-called transparent testing methods. This is especially important for modern computer systems, such as embedded systems, systems and networks on chips, on-board computer applications, network servers, and automated control systems that require periodic testing of their components. This article analyzes the effectiveness of existing transparent tests based on the use of the properties of data stored in the memory, such as changing data and their symmetry. As a new approach for constructing transparent tests, we propose to use modified address sequences with duplicate addresses to reduce the time complexity of tests and increase their diagnostic abilities.